2022
DOI: 10.20473/ijosh.v11isi.2022.58-67
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Contact Dermatitis in Metal Industrial Workers 2022

Abstract: Introduction: The metal industry plays an essential role in rapid economic growth. The growth is straight with the worker increment and high occupational disease risk. Various materials, especially in the metal industry, can initiate contact dermatitis in the workplace. Skin is the organ that exposes frequently, and skin disease is the most common disease among occupational dermatitis. Allergens and irritants exposure contribute to contact dermatitis. In Indonesia, occupational skin diseases are 97%, and Irrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…This practice is not followed by the people of West Soro'an Hamlet, which increases the risk of contracting the disease as the disease chain remains unbroken. Studies have indicated a relationship between age, gender, personal hygiene, use of personal protective equipment (PPE), contact time, contact frequency, and the incidence of contact dermatitis symptoms [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…This practice is not followed by the people of West Soro'an Hamlet, which increases the risk of contracting the disease as the disease chain remains unbroken. Studies have indicated a relationship between age, gender, personal hygiene, use of personal protective equipment (PPE), contact time, contact frequency, and the incidence of contact dermatitis symptoms [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Maintaining personal hygiene, including proper handwashing practices, is a crucial preventive measure to minimize the incidence of contact dermatitis. However, it is important to highlight that errors during handwashing can actually serve as triggers for dermatitis, particularly when hands are not thoroughly cleaned and remnants of chemicals remain on the skin surface 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Dermatitis kontak adalah penyakit kulit yang memilliki gejala klinis seperti gatal, kemerahan, muncul lepuhan yang berisi cairan, terasa nyeri. Penyebab dermatitis kontak adalah faktor eksogen dan faktor endogen [4]. Faktor eksogen meliputi lama bekerja, riwayat penyakit kulit, riwayat pekerjaan, lingkungan dan jenis pekerjaan.…”
Section: Pendahuluanunclassified